The patterns and driving forces of orbital-to millennial-timescales East Asian summer monsoon precipitation variations during the last glaciation - Yi Li; Jingwei Zhang; Xinmiao Chen; Zhi Zhang; Qingfeng Shao; Xinggong Kong; Simin Peng (CATENA, 2026)

Baicalin as an alternative to antibiotics: impact on and regulation of gut microbiota and metabolic homeostasis - Jinfeng Zhao; Xinyu Fang; Simin Wu; Peng Liao (Livestock Science, 2026)

Embryonic developmental toxicity and potential endocrine disruption in an estuarine benthic fish under binary and ternary exposures to organic ultraviolet absorbents - Yining Zhang; Jinzhi Ren; Luhang She; Chenyang Sun; Ziqiang Guan; Simin Xia; Jianjun Li; Jining Liu; Ying Peng (Environmental Pollution, 2026)

Seasonal jet stream dominates spatiotemporal heterogeneity of dry-wet status in arid Central Asia since the Holocene - Simin Peng; Yu Li; Zhansen Zhang; Zhi Zhang; Yong Ge (Global and Planetary Change, 2026)

A Study on the Mountainous Merging Precipitation Model and Effective Covariates - Mengya Xing; Simin Qu; Peng Jiang; Xing Chen; Wen Ji (Water Resources Management, 2026)

Study on the extraction, purification and anti-ageing activity of polydatin in Reynoutria japonica Houtt - Simin Yang; Xiaotong Qin; Mingwei Jia; Xiaoming Peng; Xiaoqiang Yan; Jie Guan; Ruijun Ju (Natural Product Research, 2026)

Correction to: Inhibition of USP30 Promotes Mitophagy by Regulating Ubiquitination of MFN2 by Parkin to Attenuate Early Brain Injury after SAH - Yang Liu; Chenbei Yao; Bin Sheng; Simin Zhi; Xiangxin Chen; Pengfei Ding; Jiatong Zhang; Zhennan Tao; Wei Li; Zong Zhuang; Jiannan Mao; Zheng Peng; et al. (Translational Stroke Research, 2026)

Convallatoxin ameliorates fibroblast-like synoviocytes-mediated synovial inflammation and joint destruction in rheumatoid arthritis by targeting IDH1 - Suling Liu; Huijuan Hu; Yu Kuang; Simin Chen; Kai Sun; Chenxi Peng; Ruiru Li; Fan Su; Liuqin Liang; Qian Qiu; Youjun Xiao; Hanshi Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Diverse cellulolytic bacterial community in the gut of Trypoxylus dichotomus larvae: a promising source for novel cellulose-degrading microorganisms - Ao Li; Linyao Weng; Jiajing Ye; Simin Peng; Yujie Fan; Xinqi Zhang; Qingyun Wang; Shouke Zhang; Junhao Huang (Journal of Asia-Pacific Entomology, 2026)

Acupuncture as a modulator of microglial polarization and pyroptosis in depression: evidence from a chronic unpredictable mild stress rat model - Xinhong Wu; Zhuoran You; Tiansheng Zhang; Jingyu Zeng; Meng Li; Simin Yan; Jianguo Li; Peng Li; Junliang Shen; Siyu Liu; Muhammad Shahzad Aslam; Jingxuan Li; et al. (Metabolic Brain Disease, 2026)

Spatial multiple variables and single variable updating via hydrologic system differential response method in real-time flood forecasting - Xiaoqin Zhang; Zhengyang Zhao; Rui Qin; Weimin Bao; Simin Qu; Peng Shi (Journal of Hydrology, 2025)

Soil Water Accounting Network (SWAN): a novel neural network for modeling conceptual hydrological processes - Zheng Fang; Simin Qu; Ziheng Li; Qiongfang Li; Peng Shi; Yiqun Sun; Xiaoqiang Yang; Han Tang; Junfang Zhang; Zhengxian Zhu; Hongshi Wu; Weimin Bao (Journal of Hydrology, 2025)

Investigating the mechanisms of Triclocarban-induced liver injury: A comprehensive analysisbased on network toxicology and in vivo experiments - Xinyu Fang; Jinfeng Zhao; Simin Wu; Peng Liao; Guiping Guan (Environmental Pollution, 2025)

Nutrient regulation targeting macrophage-controlled intestinal mucosal healing: A promising strategy against intestinal mucositis induced by deoxynivalenol - Simin Wu; Xinyu Fang; Jinfeng Zhao; Gang Liu; Peng Liao (Toxicon, 2025)

Ratio-fluorescence detection of propyl gallate based on MnOOH nanoflakes and β-cyclodextrin modified quantum dots - Bo Peng; Fengxiang Du; Simin Dou; Yuying Yang; Min Zhou; Shengguo Zhao; Yanjun Fang (Food Chemistry, 2025)

Embryonic developmental toxicity to estuarine fish: Single and co-exposure to EHMC and its phototransformation products in Mugilogobius chulae - Jinzhi Ren; Luhang She; Chenyang Sun; Yining Zhang; Yimeng Wang; Simin Xia; Caixia Gao; Jianjun Li; Xiangping Nie; Ying Peng (Environmental Research, 2025)

Opportunities to mitigate process-related greenhouse gas emissions in global trade networks - Simin Xu; Yunan Peng; Kejia Yan; Mengyao Han; Bo Zhang (Sustainable Production and Consumption, 2025)

Enhancing water security in lake basins through geographic intelligence technology - Yong Ge; Li Zhang; Yi Han; Die Zhang; Wenjing Yang; Lian Feng; Jinwei Dong; Shuping Wang; Simin Peng; Chaoyang Fang (Science Bulletin, 2025)

The intestinal toxicity mechanisms of triclosan and triclocarban and their possible clinical nutritional intervention mechanisms - Xinyu Fang; Jinfeng Zhao; Simin Wu; Peng Liao; Guiping Guan (Environmental Pollution, 2025)

Cerebral [18F]AIF-FAPI-42-Based PET Imaging of Fibroblast Activation Protein for Non-invasive Quantification of Fibrosis After Ischemic Stroke - Peipei Tang; Yang Liu; Simin Peng; Zhikai Cai; Ganghua Tang; Zhou Zhou; Kongzhen Hu; Yuhua Zhong (Translational Stroke Research, 2025)

The interaction of atmospheric boundary layer and PM pollution in Mongolian Plateau: Implication for the threshold control strategy - Simin Yang; Yongjing Ma; Wenyu Zhang; Zhong Lin; Zhenguo Lu; Xingjun Zhou; Yuanzhe Ren; Xinbing Ren; Kecheng Peng; Yulong Tan; Yiming Wei; Masroor Ahmad; et al. (Atmospheric Research, 2025)

Correction to: Inhibition of USP30 Promotes Mitophagy by Regulating Ubiquitination of MFN2 by Parkin to Attenuate Early Brain Injury After SAH - Yang Liu; Chenbei Yao; Bin Sheng; Simin Zhi; Xiangxin Chen; Pengfei Ding; Jiatong Zhang; Zhennan Tao; Wei Li; Zong Zhuang; Jiannan Mao; Zheng Peng; et al. (Translational Stroke Research, 2025)

Inhibition of USP30 Promotes Mitophagy by Regulating Ubiquitination of MFN2 by Parkin to Attenuate Early Brain Injury After SAH - Yang Liu; Chenbei Yao; Bin Sheng; Simin Zhi; Xiangxin Chen; Pengfei Ding; Jiatong Zhang; Zhennan Tao; Wei Li; Zong Zhuang; Jiannan Mao; Zheng Peng; et al. (Translational Stroke Research, 2025)
Subarachnoid hemorrhage (SAH) is a type of stroke with a high disability and mortality rate. Apoptosis caused by massive damage to mitochondria in neuron cells and inflammatory responses caused by high extracellular ATP lead to poor outcomes. USP30 is a deubiquitinating enzyme that inhibits mitophagy, resulting in a failure to remove damaged mitochondria in a timely manner after SAH; nevertheless, the pathway through which USP30 inhibits mitophagy is unknown. This study evaluated the neuroprotective role and possible molecular basis by which inhibiting USP30 to attenuate SAH-induced EBI by promoting neuronal mitophagy. We used an in vitro model of hemoglobin exposure and an in vivo model of intravascular perforation. Increased expression of USP30 was found after SAH in vivo and in vitro, and USP30 inhibition expression in SAH mice treated with MF094 resulted in significant improvement of neurological injury and inflammatory response and mediated good outcomes, suggesting a neuroprotective effect of USP30 inhibition. In cultured neurons, inhibition of USP30 promoted ubiquitination modification of mitochondrial fusion protein 2 (MFN2) by E3 ubiquitin ligase (Parkin), separating damaged mitochondria from the healthy mitochondrial network and prompting mitophagy, causing early clearance of damaged intracellular mitochondria, and reducing the onset of apoptosis. The high extracellular ATP environment was meliorated, reversing the conversion of microglia to a pro-inflammatory phenotype and reducing inflammatory injury. USP30 inhibition had no autophagy-promoting effect on structurally and functionally sound mitochondria and did not inhibit normal intracellular ATP production. The findings suggest that USP30 inhibition has a neuroprotective effect after SAH by promoting early mitophagy after SAH to clear damaged mitochondria.

Global dry-wet patterns under various driving factors and their applications in projecting the future - Junjie Duan; Yu Li; Simin Peng; Yuxin Zhang; Zhansen Zhang; Mingjun Gao; Yaxin Xue; Hao Shang; Shiyu Liu (Quaternary International, 2025)

Adaptive Surrogate Model Assisted Swarm Intelligence for Parameter Inversion of complex hydrological models - Guhan Li; Peng Shi; Simin Qu; Lingzhong Kong; Xiaohua Xiang; Qian Yang; Yu Qiao; Shiyu Lu (Environmental Modelling & Software, 2025)

Liposome/chitosan coating film bioplastic packaging for Litchi fruit preservation - Bodan Luo; Simin Xuan; Xiaotong Wang; Keying Ding; Peng Jin; Yonghua Zheng; Zhengguo Wu (Food Chemistry, 2025)

Interactive effects of aridity and local environmental factors on the functional trait composition and diversity of macroinvertebrate assemblages in dryland rivers - Jun Wang; Simin Bao; Jani Heino; Zhenyuan Liu; Peng Xie; Xuefei Zhong; Qiong Zhou (Science of The Total Environment, 2024)

Photothermal controlled antibacterial Ta4C3Tx-AgNPs/nanocellulose bioplastic food packaging - Xiaotong Wang; Simin Xuan; Keying Ding; Peng Jin; Yonghua Zheng; Zhengguo Wu (Food Chemistry, 2024)

A DNA walker based on hairpin-shaped DNA aligner and fueled by nicking endonuclease for sensitive and rapid miRNA analysis - Ting Huang; Zhenbang Lu; Peixian Mo; Piao Liu; Simin Liu; Jing Peng; Rongtian Li; Nuan Jia; Minmin Li; Zong Dai; Jun Chen; Jinxiang Chen (Analytica Chimica Acta, 2024)

AI model to improve the mountain boundary layer height of ERA5 - Jinyuan Xin; Kecheng Peng; Xiaoqian Zhu; Xiaole Pan; Qiyuan Wang; Junji Cao; Zifa Wang; Xiaoqun Cao; Xinbing Ren; Simin Yang; Yiming Wei; Dandan Zhao; et al. (Atmospheric Research, 2024)

Investigating the potential of EMA-embedded feature selection method for ESVR and LSTM to enhance the robustness of monthly streamflow forecasting from local meteorological information - Lei Xu; Peng Shi; Hongshi Wu; Simin Qu; Qiongfang Li; Yiqun Sun; Xiaoqiang Yang; Peng Jiang; Chao Qiu (Journal of Hydrology, 2024)

Advancing real-time error correction of flood forecasting based on the hydrologic similarity theory and machine learning techniques - Peng Shi; Hongshi Wu; Simin Qu; Xiaoqiang Yang; Ziheng Lin; Song Ding; Wei Si (Environmental Research, 2024)

A hydrologic similarity-based parameters dynamic matching framework: Application to enhance the real-time flood forecasting - Hongshi Wu; Peng Shi; Simin Qu; Xiaoqiang Yang; Hongxue Zhang; Le Wang; Song Ding; Zichun Li; Meixia Lu; Chao Qiu (Science of The Total Environment, 2024)

Multi-objective optimization of water electrolysis based on coupling model of electrochemistry and multiphase flow - Xudong Duan; Juan Xiao; Xiaocheng Peng; Shuwen Feng; Simin Wang; Jian Wen (Journal of Environmental Chemical Engineering, 2023)

Comparison of transit time models for exploring seasonal variation of preferential flow in a Moso bamboo watershed - Jianfeng Gou; Simin Qu; Peng Shi; Huade Guan; Hai Yang; Zhicai Zhang; Jintao Liu; Zhiguo Su (Journal of Hydrology, 2023)

Environmental, social, and governance (ESG) performance and financial outcomes: Analyzing the impact of ESG on financial performance - Simin Chen; Yu Song; Peng Gao (Journal of Environmental Management, 2023)

Occurrence and removal rate of typical pharmaceuticals and personal care products (PPCPs) in an urban wastewater treatment plant in Beijing, China - Jia Liu; Simin Ge; Peng Shao; Jianfeng Wang; Yanju Liu; Wei Wei; Can He; Lilan Zhang (Chemosphere, 2023)

Time-scale effects in human-nature interactions, regionally and globally - Yu Li; Mingjun Gao; Zhansen Zhang; Yuxin Zhang; Simin Peng (Journal of Geographical Sciences, 2023)

Transcriptome analysis reveals self-redox mineralization mechanism of azo dyes and novel decolorizing hydrolases in Aspergillus tabacinus LZ-M - Xuan Yu; Chunlan Mao; Simin Zong; Aman Khan; Wenxue Wang; Hui Yun; Peng Zhang; Toshiro Shigaki; Yitian Fang; Huawen Han; Xiangkai Li (Environmental Pollution, 2023)

Insights into methanogenesis of mesophilic-psychrophilic varied anaerobic digestion of municipal sludge with antibiotic stress - Hui Yun; Bin Liang; Zhangwei He; Minghan Li; Simin Zong; Zhenfei Wang; Bin Ge; Peng Zhang; Xiangkai Li; Aijie Wang (Journal of Environmental Management, 2023)

Effect of Distinct Evaluation Objectives on Different Precipitation Downscaling Methods and the Corresponding Potential Impacts on Catchment Runoff Modelling - Xumin Zhang; Simin Qu; Jijie Shen; Yingbing Chen; Xiaoqiang Yang; Peng Jiang; Peng Shi (Water Resources Management, 2023)

Seasonal variation of transit time distribution and associated hydrological processes in a Moso bamboo watershed under the East Asian monsoon climate - Jianfeng Gou; Simin Qu; Huade Guan; Peng Shi; Zhicai Zhang; Hai Yang; Jintao Liu; Zhiguo Su; Xiaole Han (Journal of Hydrology, 2023)

Unraveling the effects of the particle size on biomass properties, microbial community, and functional genes of denitrifying granular sludge - Zhaozhao Wang; Shuhao Zhu; Simin Li; Jun Ma; Jing Zhang; Peng Gao; Lina Yan (Journal of Environmental Chemical Engineering, 2023)

Spiral donor-based host materials for highly efficient blue thermally activated delayed fluorescence OLEDs - Deli Li; Mengke Li; Wei Li; Wenqi Li; Zijian Chen; Xiaomei Peng; Denghui Liu; Guo-Xi Yang; Simin Jiang; Yiyang Gan; Zhihai Yang; Kunkun Liu; et al. (Chemical Engineering Journal, 2023)

Reduction of metronidazole in municipal wastewater and protection of activated sludge system using a novel immobilized Aspergillus tabacinus LZ-M - Xuan Yu; Chunlan Mao; Wenxue Wang; Saurabh Kulshrestha; Peng Zhang; Muhammad Usman; Simin Zong; Mian Gul Hilal; Yitian Fang; Huawen Han; Xiangkai Li (Bioresource Technology, 2023)

Paleoclimatic proxies from global closed basins and the possible beginning of Anthropocene - Yu Li; Qin Han; Lu Hao; Xinzhong Zhang; Dawei Chen; Yuxin Zhang; Lingmei Xu; Wangting Ye; Simin Peng; Yichan Li; Zhuowen Feng; Hebin Liu (Journal of Geographical Sciences, 2021)

A dynamic information extraction method for areal mean rainfall error and its application in basins of different scales for flood forecasting - Wei Si; Hua Zhong; Peng Jiang; Weimin Bao; Peng Shi; Simin Qu (Stochastic Environmental Research and Risk Assessment, 2021)

A continuous simulation of Holocene effective moisture change represented by variability of virtual lake level in East and Central Asia - Yu Li; Yuxin Zhang; Xinzhong Zhang; Wangting Ye; Lingmei Xu; Qin Han; Yichan Li; Hebin Liu; Simin Peng (Science China Earth Sciences, 2020)

The protective microRNA-199a-5p-mediated unfolded protein response in hypoxic cardiomyocytes is regulated by STAT3 pathway - Yang Zhou; Bo Pang; Yingbin Xiao; Simin Zhou; Bin He; Fan Zhang; Wei Liu; Huali Peng; Peng Li (Journal of Physiology and Biochemistry, 2019)

Temporal 18 O and deuterium variations in hydrologic components of a small watershed during a typhoon event - Simin Qu; Yifan Wang; Minmin Zhou; Han Liu; Peng Shi; Zhongbo Yu; Long Xiang (Isotopes in Environmental and Health Studies, 2017)

Spatial Distribution and Temporal Trends in Precipitation Concentration Indices for the Southwest China - Peng Shi; Miao Wu; Simin Qu; Peng Jiang; Xueyuan Qiao; Xi Chen; Mi Zhou; Zhicai Zhang (Water Resources Management, 2015)

Spatial distribution and temporal trends in daily and monthly precipitation concentration indices in the upper reaches of the Huai River, China - Peng Shi; Xueyuan Qiao; Xi Chen; Mi Zhou; Simin Qu; Xinxin Ma; Zhicai Zhang (Stochastic Environmental Research and Risk Assessment, 2014)

Differences in oxygen-18 and deuterium content of throughfall and rainfall during different flood events in a small headwater watershed - Simin Qu; Minmin Zhou; Peng Shi; Han Liu; Weimin Bao; Xi Chen (Isotopes in Environmental and Health Studies, 2014)

Evaluating Infiltration Mechanisms Using Breakthrough Curve and Mean Residence Time - Qu Simin; Wang Tao; Bao Weimin; Shi Peng; Jiang Peng; Zhou Minmin; Yu Zhongbo (Water Resources Management, 2013)

Effects of Land-Use and Climate Change on Hydrological Processes in the Upstream of Huai River, China - Peng Shi; Xinxin Ma; Yuanbing Hou; Qiongfang Li; Zhicai Zhang; Simin Qu; Chao Chen; Tao Cai; Xiuqin Fang (Water Resources Management, 2013)

Evaluating the SWAT Model for Hydrological Modeling in the Xixian Watershed and a Comparison with the XAJ Model - Peng Shi; Chao Chen; Ragahavan Srinivasan; Xuesong Zhang; Tao Cai; Xiuqin Fang; Simin Qu; Xi Chen; Qiongfang Li (Water Resources Management, 2011)